Landscape and Stand Characteristics Influence on the Bird Assemblage in Nothofagus antarctica Forests of Tierra del Fuego - Benitez, Julieta; Barrera, Marcelo Daniel; Rosas, Yamina Micaela; Martínez Pastur, Guillermo José; Lencinas, María Vanessa (Land)
Different variables operate simultaneously at different spatial scales, influencing community composition and species distribution. This knowledge could improve management and conservation practices in managed menaced forests. The objective of this work was to determine the influence of landscape and stand variables on the bird assemblage of the managed Nothofagus antarctica forest of Tierra del Fuego (Argentina). We used data from bird point counts (three or four censuses during middle summer of two consecutive years) located at 48 sites distributed at four ranches. At each site, we extracted landscape variables with Fragstat software from the forest patches, the cover classes, and the whole landscape. We also evaluated local stand characteristics, such as forest structure, ground cover, and food availability, including understory plant cover usually consumed by birds and available arthropods. Data were evaluated by detrended and canonical correspondence analyses. We found that landscape configuration (e.g., forest patch shape) and local stand variables (e.g., canopy cover) influenced bird assemblage more than landscape composition. Moreover, bird functional groups responded differently to different spatial scale variables (e.g., forest specialist species were associated with forest structure, but species that use low strata to nest and feed were associated with landscape configuration variables), demonstrating the importance of using multiple spatial scales to better understand bird species requirements. The combination of practices that promote some local characteristics (e.g., high canopy cover) and more complex landscape configurations could simultaneously favor different bird species groups and improve the effectiveness of management and conservation strategies. Fil: Benitez, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Barrera, Marcelo Daniel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. ...